The Effect of the Fraud Triangle and Sharia Compliance Disclosure on Financial Statement Fraud in Indonesian Islamic Banks - Dhea Marella Aulia; Muhammad Farhan; Agil Novriansa; Christian Damar Sagara Sitepu (Облік і фінанси)
Financial statement fraud in Islamic banks is unethical because, in this way, banks mislead their shareholders and other users of financial statements. Applying Sharia rules in Islamic institutions is an effort to prevent fraud in financial statements. Three conditions generally arise when fraud occurs: management under pressure, lack of control, and a group of people involved in rationalizing fraud. This study will analyze the relationship between the fraud triangle and Sharia compliance disclosure in minimizing and detecting financial statement fraud in Indonesian Islamic banks. This study aims to determine how these variables influence financial statement fraud, using the F-score as a measurement. This quantitative research utilizes secondary data from the official websites of Islamic banks. The population and sample for this study comprise Islamic banks in Indonesia from 2018 to 2023. The research uses a logistic regression method to analyze the data. The study results showed that financial stability (proxied by bank asset changes) and Islamic income ratio do not impact financial statement fraud. Instead, the presence of an independent board of commissioners who supervise objectively and effectively can influence company management in minimizing the risk of fraud in financial statement presentations. Additionally, changing auditors increases the likelihood of detecting potential fraud in financial statements. Sharia compliance disclosure also significantly increases the reliability of financial reporting data and indicates a high level of corporate responsibility for the Islamic bank to shareholders and society. The management of Islamic banks can use the results of this study to understand the determinants of financial statement fraud better.